Answer:
The second one (B)
Step-by-step explanation:
u don't multiply a number by the same number if u know what I mean
hope this helps <3
Send me your email I will send the working.
The answers:
x = 1
y = -5
Answer:
![d_{AB}\ne d_{JK}](https://tex.z-dn.net/?f=d_%7BAB%7D%5Cne%20d_%7BJK%7D)
![d_{AB}\ne \:d_{GH}](https://tex.z-dn.net/?f=d_%7BAB%7D%5Cne%20%5C%3Ad_%7BGH%7D)
![d_{GH}\ne \:d_{JK}](https://tex.z-dn.net/?f=d_%7BGH%7D%5Cne%20%5C%3Ad_%7BJK%7D)
Therefore,
Option (A) is false
Option (B) is false
Option (C) is false
Step-by-step explanation:
Considering the graph
Given the vertices of the segment AB
Finding the length of AB using the formula
![d_{AB}\:=\:\sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}](https://tex.z-dn.net/?f=d_%7BAB%7D%5C%3A%3D%5C%3A%5Csqrt%7B%5Cleft%28x_2-x_1%5Cright%29%5E2%2B%5Cleft%28y_2-y_1%5Cright%29%5E2%7D)
![=\sqrt{\left(2-\left(-4\right)\right)^2+\left(5-4\right)^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%5Cleft%282-%5Cleft%28-4%5Cright%29%5Cright%29%5E2%2B%5Cleft%285-4%5Cright%29%5E2%7D)
![=\sqrt{\left(2+4\right)^2+\left(5-4\right)^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%5Cleft%282%2B4%5Cright%29%5E2%2B%5Cleft%285-4%5Cright%29%5E2%7D)
![=\sqrt{6^2+1}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B6%5E2%2B1%7D)
![=\sqrt{36+1}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B36%2B1%7D)
![=\sqrt{37}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B37%7D)
![d_{AB}\:=\sqrt{37}](https://tex.z-dn.net/?f=d_%7BAB%7D%5C%3A%3D%5Csqrt%7B37%7D)
units
Given the vertices of the segment JK
From the graph, it is clear that the length of JK = 5 units
so
units
Given the vertices of the segment GH
Finding the length of GH using the formula
![d_{GH}\:=\:\sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}](https://tex.z-dn.net/?f=d_%7BGH%7D%5C%3A%3D%5C%3A%5Csqrt%7B%5Cleft%28x_2-x_1%5Cright%29%5E2%2B%5Cleft%28y_2-y_1%5Cright%29%5E2%7D)
![=\sqrt{\left(-2-\left(-5\right)\right)^2+\left(-2-\left(-2\right)\right)^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%5Cleft%28-2-%5Cleft%28-5%5Cright%29%5Cright%29%5E2%2B%5Cleft%28-2-%5Cleft%28-2%5Cright%29%5Cright%29%5E2%7D)
![=\sqrt{\left(5-2\right)^2+\left(2-2\right)^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%5Cleft%285-2%5Cright%29%5E2%2B%5Cleft%282-2%5Cright%29%5E2%7D)
![=\sqrt{3^2+0}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B3%5E2%2B0%7D)
![=\sqrt{3^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B3%5E2%7D)
![\mathrm{Apply\:radical\:rule\:}\sqrt[n]{a^n}=a,\:\quad \mathrm{\:assuming\:}a\ge 0](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3Aradical%5C%3Arule%5C%3A%7D%5Csqrt%5Bn%5D%7Ba%5En%7D%3Da%2C%5C%3A%5Cquad%20%5Cmathrm%7B%5C%3Aassuming%5C%3A%7Da%5Cge%200)
units
Thus, from the calculations, it is clear that:
Thus,
![d_{AB}\ne d_{JK}](https://tex.z-dn.net/?f=d_%7BAB%7D%5Cne%20d_%7BJK%7D)
![d_{AB}\ne \:d_{GH}](https://tex.z-dn.net/?f=d_%7BAB%7D%5Cne%20%5C%3Ad_%7BGH%7D)
![d_{GH}\ne \:d_{JK}](https://tex.z-dn.net/?f=d_%7BGH%7D%5Cne%20%5C%3Ad_%7BJK%7D)
Therefore,
Option (A) is false
Option (B) is false
Option (C) is false